Role of ocean tidal asymmetry and estuarine geometry in the fate of plastic debris from ocean sources within tidal estuaries. (30th September 2021) - Núñez, Paula; Castanedo, Sonia; Medina, Raúl
Abstract: Tidal asymmetry drives the transport of materials (e.g. plastic debris) within tidal estuaries. Most previous research has focused on the asymmetry that arises within estuaries and relates to sediment transport; however, estuaries exhibiting tidal asymmetry at the mouth and their relationship with materials other than sediments have received less attention. This study uses numerical hydrodynamic and Lagrangian transport models to assess the effect of estuary morphology on the propagation of asymmetric tides and how it influences the distribution of plastic debris that reaches tidal estuaries from ocean sources. A series of numerical experiments were conducted in idealised estuaries, specifically in tidal creeks. The results show that the asymmetry at the mouth results in flood/ebb dominance and influences the presence of plastic debris in areas where the main channel favours tidal flow. Flood-dominated estuaries show an import capacity 50% higher than those that show symmetric or negative asymmetric tides at their mouths. Numerical simulations show that the relevant role in defining flood or ebb dominance is played by the geometry of the estuary when increased friction that opposes flow and intertidal storage areas are present, although small influences of the external tidal asymmetry are also appreciated. The probability of plastic debris presence was 90% for positive asymmetric tides and varied between and 70%–80% for symmetric and negative-asymmetric tides. A remarkable finding of this study is the regulatory role of kurtosis which corrects the tendency induced by skewness in the fate of plastic debris. These findings were corroborated with the application of this methodology to a real estuary and a comparison of the obtained results with available field data on plastic debris. Graphical abstract: Highlights: Estuary tidal asymmetry depends on estuary morphology and ocean tidal asymmetry. Tidal skewness and kurtosis define plastic accumulation areas in tidal estuaries. Positive-asymmetric tides lead to an estuarine import of plastics from oceans.